Factors related to health-related quality of life in patients with acute coronary syndrome in West Java, Indonesia: A correlational study - Haerul Imam; Chanokporn Jitpanya (Belitung Raya Foundation, Indonesia, 2022)
Background: Although acute coronary syndrome impacts patients’ health-related quality of life, a dearth of studies explore this issue in Indonesia. Thus, understanding factors associated with health-related quality of life among patients with acute coronary syndrome is a necessity. Objective: This study aimed to examine the relationships between age, pain, dyspnea, functional status, self-efficacy, social support, and health-related quality of life in patients with acute coronary syndrome in West Java, Indonesia. Methods: This study employed a descriptive correlational study involving 186 patients with acute coronary syndrome purposively selected in the outpatient clinics of the top referral public hospital. Data were collected in 2020 using validated instruments: Rose Questionnaire for Angina (RQA), Rose Dyspnea Scale (RDS), Seattle Angina Questionnaire (SAQ), General Self-efficacy Scale (GSE), ENRICHD Social Support Instrument (ESSI), and MacNew Health-Related Quality of Life. Data were analyzed using descriptive statistics and Spearman-rank correlation. Results: Overall, the health-related quality of life in patients with acute coronary syndrome was high (Mean = 4.97, SD = 0.92), including in its subscales: emotional (Mean = 4.94, SD = 0.88), physical (Mean = 5.07, SD = 1.12), and social (Mean = 5.05, SD = 1.55) subscales. Significant factors related to health-related quality of life were pain (r = 0.296, p <0.001), functional status (r = 0.601, p <0.001), dyspnea (r = -0.438, p<0.001), and self-efficacy (r = 0.299, p <0.001). Meanwhile, age and social support had no significant relationships with health-related quality of life (p = 0.270, p = 0.059). Interestingly, social support was significantly correlated with the emotional subscale of health-related quality of life (r = 0.156, p = 0.034). Conclusion: Functional status, pain, and self-efficacy were positively correlated with health-related quality of life, while dyspnea had a negative association. This finding serves as basic information for nurses and other healthcare professionals to consider the related factors identified in this study to improve nursing interventions in order to increase health-related quality of life among patients with acute coronary syndrome.